2005
DOI: 10.1111/j.1471-4159.2005.03368.x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes as antigen‐presenting cells: expression of IL‐12/IL‐23

Abstract: Interleukin-12 (IL-12, p70) a heterodimeric cytokine of p40 and p35 subunits, important for Th1-type immune responses, has been attributed a prominent role in multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE). Recently, the related heterodimeric cytokine, IL-23, composed of the same p40 subunit as IL-12 and a unique p19 subunit, was shown to be involved in Th1 responses and EAE. We investigated whether astrocytes and microglia, CNS cells with antigen-presenting cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 60 publications
3
78
1
1
Order By: Relevance
“…Some studies indicated that these cells express IL12p40, but not the p70 holoprotein (26). Other studies indicated that astrocytes are capable of producing both IL-12p40 and IL12p70 (27). The present studies indicate that astrocytes constitutively express little or no IL-12p40 (Fig.…”
Section: Effects Of Ppar-␥ Agonists On Il-12 Family Subunit Mrna Exprsupporting
confidence: 56%
“…Some studies indicated that these cells express IL12p40, but not the p70 holoprotein (26). Other studies indicated that astrocytes are capable of producing both IL-12p40 and IL12p70 (27). The present studies indicate that astrocytes constitutively express little or no IL-12p40 (Fig.…”
Section: Effects Of Ppar-␥ Agonists On Il-12 Family Subunit Mrna Exprsupporting
confidence: 56%
“…Furthermore, astrocytic iNOS has been demonstrated in MS lesions, and it is recognized as an important pathogenic feature of MS [82]. [57,61,81,[83][84][85][86][87]. Thus, astrocytes could be involved in the complexity of cytokine functions in MS pathogenesis [88].…”
Section: Enemies Within and Friends In Needmentioning
confidence: 99%
“…Angiogenesis is regulated by multiple positive-and negative-regulatory factors, including vascular endothelial growth factor (VEGF), angiopoitins, interferons (alpha/beta/gamma), IL-12, tissue inhibitory metalloproteinase (TIMP)-3 and transforming growth factor-beta 1 (Campbell et al, 1999;Rivieccio et al, 2005;Zeinstra et al, 2006;Constantinescu et al, 2005;Muir et al, 2002;Dhandapani, 2005;Carmeliet, 2000;Petersen et al, 2005;Sidky and Borden, 1987;Raza and Cornelius, 2000;Dhandapani et al, 2005Dhandapani et al, , 2007. VEGF, a prototypical angiogenic growth factor, regulates cell proliferation, vascular permeability, chemotaxis, and survival of ECs and vasculogenesis and angiogenesis in the developing embryo (Ferrara et al, 2003).…”
Section: Introductionmentioning
confidence: 99%